2020
DOI: 10.1002/1878-0261.12759
|View full text |Cite
|
Sign up to set email alerts
|

The BCL‐2 family protein inhibitor ABT‐737 as an additional tool for the treatment of EBV‐associated post‐transplant lymphoproliferative disorders

Abstract: Post-transplant lymphoproliferative disorders (PTLD) and Burkitt's lymphoma (BL) are B-cell malignancies strongly associated with Epstein-Barr virus (EBV) infection. In these lymphoproliferative disorders, EBV infection induces an increase in the expression of the anti-apoptotic protein BCL-2. Given its chemoprotective effect, BCL-2 constitutes an attractive target for new therapeutic strategies for EBV-positive B-cell malignancies. Here, we show that ABT-737, a small inhibitor of BCL-2, BCL-X(L), and BCL-w, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Accumulating evidence has shown that deceased ratio of antiapoptotic member Bcl-2 and pro-apoptotic Bax contribute to mitochondrial dysfunction and apoptosis (Robert et al, 2020). This is because that increase in Bcl-2 /Bax ratio prohibits Bax translocation to the mitochondria and then prevents cells from apoptotic (Yu et al, 2003).…”
Section: Copper Played a Deleterious Role In Ht22 Cells Via Pcreb/bdn...mentioning
confidence: 99%
“…Accumulating evidence has shown that deceased ratio of antiapoptotic member Bcl-2 and pro-apoptotic Bax contribute to mitochondrial dysfunction and apoptosis (Robert et al, 2020). This is because that increase in Bcl-2 /Bax ratio prohibits Bax translocation to the mitochondria and then prevents cells from apoptotic (Yu et al, 2003).…”
Section: Copper Played a Deleterious Role In Ht22 Cells Via Pcreb/bdn...mentioning
confidence: 99%
“…The BCL-2 family members are located on the mitochondria and can control its permeability, the release of cytochrome C, the activation of “priming” CASP-9, and the subsequent activation of “executive” CASP-3. Endogenous apoptosis can be inhibited through prosurvival signaling pathways such as PI3K/AKT and MAPK [ 31 , 32 ]. The PI3K/AKT pathway is an intracellular signaling pathway with phosphatidylinositol kinase and serine/threonine kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN has a negative regulatory effect on the PI3K/AKT pathway [ 34 ]. Activated AKT can phosphorylate and inhibit Bad, BAX, CASP-9, GSK-3, and FOXO1 [ 32 ]. Western blot and RT-qPCR results showed that GLSP downregulated the expression of PI3K and p-AKT genes and proteins in H22 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although their use in PTLD has been very limited, there seems to be a strong in vitro rationale in PTLD as well. 65,66 In addition, some of these molecules, including the Bruton tyrosine kinase inhibitor ibrutinib, may also be effective in graft rejection.…”
Section: Small Moleculesmentioning
confidence: 99%